(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Plantar fasciitis leading cause of heel pain, frequently affects individuals engaged in prolonged standing, such as salespersons. The interplay between intrinsic foot muscle (IFM) strength and ankle foot dorsiflexion is critical in maintaining plantar fascia integrity and reducing mechanical overload. Objective: A review on the role of IFM strength and ankle dorsiflexion in plantar fascia health, emphasizing occupational implications for salespersons. Methods: A narrative review after studying databases including PubMed, Scopus and Google Scholar (2020–2025). Studies examining the relationship between IFM function, ankle dorsiflexion, and plantar fasciopathy were analyzed. Results: Limited dorsiflexion and weak intrinsic musculature increase plantar fascia strain via altered arch mechanics and early heel-off during gait. IFM-strengthening exercises and dorsiflexion mobility programs significantly improve symptoms, posture, and foot function. Salespersons exhibit elevated plantar fasciitis prevalence due to prolonged standing and cumulative load. Conclusion: Optimal plantar fascia health relies on adequate IFM strength and ankle mobility. Integrating strengthening, stretching, and ergonomic interventions offers preventive and therapeutic benefits for salespersons.